2017
DOI: 10.1186/s12199-017-0618-7
|View full text |Cite
|
Sign up to set email alerts
|

Paraben exposure and semen quality of Japanese male partners of subfertile couples

Abstract: ObjectivesPossible relationship between semen quality (semen volume, sperm concentration and sperm motility) and parabens exposure was investigated in male partners of couples who visited a gynecology clinic in Tokyo for infertility consultation (n = 42, 36.8 ± 5.4 years).MethodsSemen parameters were measured according to WHO guideline at the clinic, and urinary methyl- (MP), ethyl- (EP), propyl- (PP) and butyl (BP) paraben concentrations were measured with liquid chromatography-tandem mass spectrometry.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 24 publications
(45 reference statements)
0
13
0
Order By: Relevance
“…There were five studies identified studying the association of parabens with semen quality and oxidative stress [ 42 , 71 , 72 , 73 , 74 ]. Only two studies revealed the correlation of urinary paraben concentrations with a low sperm count and decreased motility [ 42 , 74 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were five studies identified studying the association of parabens with semen quality and oxidative stress [ 42 , 71 , 72 , 73 , 74 ]. Only two studies revealed the correlation of urinary paraben concentrations with a low sperm count and decreased motility [ 42 , 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Jurewicz et al, found a strong correlation between urinary paraben concentrations and an increase in the abnormal morphology percentage and DNA fragmentation of spermatozoa, as well as a decrease in serum testosterone levels [ 42 ]. In studies where no correlation was revealed, there was temporal intraindividual variability [ 71 ], or the sample size was small [ 72 ], or the average age of men was low, suggesting that in young men, urinary parabens may not negatively affect their reproductive function [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the extensive epidemiological literature on associations between exposure to specific EDCs present in PCPs and semen quality, results are widely inconsistent and mostly fail to reproduce the effects observed in animal models [ 5 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. While a small number of previous studies have indicated a connection between measured levels of parabens, phthalates, glycol ethers, benzophenone UV filters, triclosan and bisphenol A, and semen characteristics, the overall evidence remains limited for these compounds [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among 42 male partners (36.8 + 5.4 years old) of couples who visited a gynecology clinic in Tokyo for infertility consultation, no significant association was found between semen parameters (sperm volume, concentration and motility) and urinary paraben concentrations in regression analyses. 151 The GM urinary concentrations of Methylparaben, Ethylparaben, Propylparaben, and Butylparaben were 48.2, 1.88, 1.13, and 0.184 ng/mL, respectively.…”
Section: Cross-sectional Studiesmentioning
confidence: 93%